Cellulosic rich biomass production with optimized process parameters by using glycerol pretreatment for biofuels applications - Sulaiman M.; Mahmood H.; Khan H.M.; Iqbal T.; Khan N.U.; Abbas M.M.; Nur-E-Alam M.; Soudagar M.E.M. (Elsevier Ltd, 2025)
In this work, we conduct acidified aqueous glycerol pre-treatment (AAG) on rice husks (RH) and utilize the response surface methodology (RSM) to assess the impact of pre-treatment parameters. The primary objective of this research is to optimize the parameters to maximize the cellulose content within RH. The parameters under consideration encompassed temperature (ranging from 80 to 110 C), retention time (spanning 15 to 45 min), and biomass loading (varying from 5 to 10 wt. %). To achieve this optimization, we perform the Box-Behnken Design (BBD) within the framework of RSM. Additionally, we scrutinize the interactive effects of these parameters on cellulose content. Our findings unveiled a remarkable increase in cellulose content, escalating from 40 % in untreated RH to an impressive 75 % in pre-treated RH under the optimized conditions of 110 C for 45 min with a 5.0 wt. % biomass loading. To further evaluate the effectiveness of the pre-treatment process, we conduct scanning electron microscopy (SEM) and X-ray diffraction (XRD) analyses, shedding light on alterations in surface morphology and crystallinity of RH. This investigation yields valuable insights, presenting novel opportunities for the efficient conversion of readily available rice husks into high-value products, such as biofuels and composites. ? 2024 The Authors